Catalytic Activities of Fe3+- and Zn2+-Natural Zeolite on the Direct Cyclisation-Acetylation of (R)-(+)-Citronellal - Edy Cahyono; M. Muchalal; Triyono Triyono; Harno Dwi Pranowo (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2014)
Characterisation and catalytic ativities investigation of modified natural zeolite on cyclisation acetylation reaction of (R)-(+)-citronellal was performed. The experimental work involved isolation of (R)-(+)-citronellal from Java Citronella oil (Cymbopogon winterianus) by vacuum fractional distillation, determination of its enantiomer, preparation and characterisation of different catalysts i.e. H-natural zeolite (H-Za), Fe3+-natural zeolite (Fe3+-Za), and Zn2+-natural zeolite (Zn2+-Za), followed by examination of catalytic activity and selectivity. Isolated citronellal contained 88.21% ee of (R)-(+)-citronellal. The main products of cyclisation-acetylation of (R)-(+)-citronellal was IPA (isopulegyl acetate) and NIPA (neo-isopulegyl acetate). Although the highest yield of IPA and NIPA was obtained by Fe3+-Za catalyst (78.69%) at 80oC and 120 min, the stereoselectivity of Fe3+-Za slightly lower than that of Zn2+-Za. Structure elucidation of citronellal and products was carried out by means of GC and GC-MS. Lewis acidity plays the role of acetyl ionic formation from acetic anhydride. The Activity and stereoselectivity of catalysts depended on Lewis acidity and cation distribution on the catalyst surface. © 2014 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)